2008
DOI: 10.1159/000112609
|View full text |Cite
|
Sign up to set email alerts
|

Results of Varicocelectomy in Patients with Isolated Teratozoospermia

Abstract: Introduction: Isolated teratozoospermia is rarely encountered in patients with clinically palpable varicocele, and the consequences of varicocelectomy remain unclear in these cases. In the current study, we assessed the effect of varicocelectomy on sperm morphology in a series of patients with infertility. Materials and Methods: The data obtained from 52 primary subfertile men with isolated teratozoospermia and clinical palpable varicocele were reviewed retrospectively. Varicocelectomy was performed on 29 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…After stratification, men with normal sperm counts had no significant improvements in sperm parameters and 21% (10/46) became oligospermic afterwards 80. A separate report of subfertile men with isolated teratozoospermia and clinical varicocele by Cakan et al showed significant improvement in all sperm parameters and spontaneous pregnancy rate of 18% (5/29) after subinguinal repair in comparison to those who decided against surgery who had no improvements in semen analysis and no pregnancies (0/23) in the follow up period (12 months) 81. These results only further underline the need for controlled studies that have less confounding variables that may influence the significance of the data.…”
Section: Varicocele Repair and Effect On Semen Analysis Profilementioning
confidence: 98%
“…After stratification, men with normal sperm counts had no significant improvements in sperm parameters and 21% (10/46) became oligospermic afterwards 80. A separate report of subfertile men with isolated teratozoospermia and clinical varicocele by Cakan et al showed significant improvement in all sperm parameters and spontaneous pregnancy rate of 18% (5/29) after subinguinal repair in comparison to those who decided against surgery who had no improvements in semen analysis and no pregnancies (0/23) in the follow up period (12 months) 81. These results only further underline the need for controlled studies that have less confounding variables that may influence the significance of the data.…”
Section: Varicocele Repair and Effect On Semen Analysis Profilementioning
confidence: 98%
“…23 Murat Çakan et al found improvement of normal morphology after surgery and during the follow-up. 24 Barbalis et al also found improved semen morphology after varicocelectomy. 25 The present study showed that 9 among 45 patients had abnormal sperm morphology and their preoperative mean semen morphology was 1.0±1.2%.…”
Section: Discussionmentioning
confidence: 93%
“…Cakan M et al studied impact of varicocelectomy on sperm morphology and found that sperm morphology improves following varicocelectomy. 20 Senbanjo RO et al, also showed that varicocelectomy results in improvement of semen quality in about 53% of patients. 21 Many studies have shown that varicocelectomy results in improvement of many semen parameters viz sperm count, sperm motility, sperm morphology and ultimately pregnancy rates.…”
Section: Discussionmentioning
confidence: 95%